Comparison of platelet rich plasma versus fibrin glue on colonic anastomoses in rats - Daglioglu,Yusuf Kenan (2018)
Abstract Purpose: To compare platelet rich plasma (PRP) and fibrin glue about the effect of anastomotic healing. Methods: Thirty six Wistar-Albino male rats diveded into 3 groups according to control(Group1), PRP (Group 2) and fibrin glue(Tisseel VH) (Group 3). The colon was transected with scissor and subsequently an end to end anastomosis was performed using continuous one layer 6/0 vicryl sutures. Postoperative 7th day effect of anastomotic healing measuring with tissue hydroxyproline(TH) level and anastomotic bursting pressure(ABP); moreover comparison of cytokine (IL-6 and IL-10) and procalcitonin levels on 1st,3rd and 7th days. Results: There was no statistically significant difference of the ABP and hydroxyproline levels between PRP and fibrin glue on the 7th day. There was no statistically significant difference between levels of proinflammatory cytokine (IL-6) (P=0.41), anti-inflammatory cytokine (IL-10) (P=0.35), and procalcitonin levels (P=0.63) on 1, 3 and 7 days. Conclusion: Fibrin glue and platelet rich plasma are shown to be effective in healing intestinal anastomoses without superior to each other.